Analysis of thickness of the epithelial in the cure of oral mucositis due to chemotherapy using 25% pegagan leaf (centella asiatica) extract gel spray - Avena Dwi Kunfiar; Rina Kartika Sari; Rahmawati Sri Praptingingsih; Rizki Amalina (Jurnal Medali, 2023)
Background: Cancer treatment with radiotherapy or chemotherapy can cause oral mucositis. Pegagan leaf extract is an herbal alternative with minimal side effects and doesn’t interfere with treatment procedures from chemotherapy cause contains triterpenoid acid, asiaticoside acid, madecoside acid, and saponins that stimulate collagen synthesis which affects epithelialization. This study aims to the difference in epithelial thickness between the administration of 25% pegagan leaf extract (Centella asiatica) spray gel and Gengigel® Hyaluronic acid spray to the healing process of oral mucositis in chemotherapy-induced rats.Method: The design of this study was an experimental laboratory using a post-test only control group design, consisting of 2 groups, namely a positive control group using Gengigel® Hyaluronic acid spray, a group of 25% pegagan leaf extract (Centella asiatica) gel spray. The statistical analysis of the study used the Independent T-test.Result: The results of the spray gel thickness of pegagan leaf extract (Centella asiatica) were 25% greater than Gengigel® Hyaluronic acid spray. The results of the Independent T-test were significant, with a value of p = 0.000 (P <0.05).Conclusion: It can be concluded that there was differences in the increase of epithelial thickness in the application of 25% pegagan leaf extract (Centella asiatica) gel spray with Gengigel® Hyaluronic acid spray on the healing of oral mucositis due to chemotherapy.